A novel approach for quantification of the future unmet medical need in right ventricular dysfunction. Issue 5 (May 2022) - Schramm, Lena K.; Monsefi, Nadejda; Hüser, Jörg; Truebel, Hubert; Mondritzki, Thomas
Highlights: There is no consistent approach to determine the UMN in complex diseases, such as RVD. Right heart failure is associated with increased morbidity and mortality while no selective therapy exists. RVD is an UMN in patients with heart failure and thus a relevant therapeutic target. Learnings might guide decision making in future drug discovery projects. Abstract : Although 'unmet medical need' (UMN) is an increasingly used term in the healthcare sector instrumental to the approximate value of drug discovery projects relevant to portfolio management, no standardized approach exists for its quantification. Especially in diseases with different comorbidities, high patient heterogeneity, and incomplete epidemiological data, it is difficult to judge the need for new therapies. The approach presented here combines an expert assessment of key UMN indicators related to the individual patient with a literature search to collect epidemiological data describing the corresponding patient population with its underlying heterogeneity. This assessment supports decision-making within the portfolio management process in larger research and development organizations.